Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.2174/156802607782340975
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Potential of Neuropeptide Y Receptor Ligands in the Treatment of Epilepsy

Abstract: A substantial amount of experimental evidence implicates neuropeptide Y (NPY) in the pathophysiology of epilepsy. Over the past 20 years, remarkable progress has been made in unraveling the mechanisms and receptors involved in the anticonvulsant effect of this abundantly expressed neuropeptide. Activation of Y(2) and/or Y(5) receptors and blockade of Y(1) receptors in the central nervous system suppresses seizures in a variety of animal seizure models. Orally available, brain penetrating Y(2) and/or Y(5) agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 196 publications
(249 reference statements)
0
6
0
2
Order By: Relevance
“…Experiments with Y2 knockout mice and overexpression of the selective Y2 ligand NPY13-36 suggest that Y2 receptor is also involved in the suppression of seizures [74,75]. In line with these studies, Y1 antagonists, and Y2 and Y5 agonists were suggested to have antiepileptic potential [76]. Indeed, a large number of different peptide derivatives of NPY were tested in animal models of epilepsy supporting this suggestion [60].…”
Section: Neuropeptide Ymentioning
confidence: 95%
“…Experiments with Y2 knockout mice and overexpression of the selective Y2 ligand NPY13-36 suggest that Y2 receptor is also involved in the suppression of seizures [74,75]. In line with these studies, Y1 antagonists, and Y2 and Y5 agonists were suggested to have antiepileptic potential [76]. Indeed, a large number of different peptide derivatives of NPY were tested in animal models of epilepsy supporting this suggestion [60].…”
Section: Neuropeptide Ymentioning
confidence: 95%
“…Development of novel oral and parental drug delivery strategies may allow brain access of NPY receptor ligands in a clinical setting. 30 …”
Section: Npy and Modulation Of Emotion Andmentioning
confidence: 99%
“…Selective NPY receptor antagonists have been developed with the aim of being new treatment for a variety of conditions including anxiety, sleep disorders, eating disorders, in addition to epilepsy (Ortiz et al., 2007; Wiater et al., 2011; Wu et al., 2011; van Raay et al., 2012). However, the barriers to clinical development have been developing compounds that are orally active, have sufficiently long half‐life, and cross the blood–brain barrier (Meurs et al., 2007). One potential approach to overcome these barriers is to use viral‐based gene therapy, focally administered into epileptogenic brain regions that selectively up‐regulate NPY expression.…”
Section: Neuropeptide Modulators Of Synaptic Neurotransmissionmentioning
confidence: 99%